Budgeting Costs and Returns for Indian River Citrus Production, 2002-03 - Ronald P. Muraro; John W. Hebb; Ed W. Stover (EDIS, 2003)
Estimated costs and returns of growing seedless grapefruit in the Indian River area of Florida are presented for the twentieth year. The format presented may be used by individual growers to budget costs and returns, utilizing individual data on specific groves.